Mitochondrial dynamics in the pathogenic mold Aspergillus fumigatus: therapeutic and evolutionary implications. Issue 5 (18th September 2015) - Neubauer, Michael; Zhu, Zhaojun; Penka, Mirjam; Helmschrott, Christoph; Wagener, Nikola; Wagener, Johannes
Summary: Mitochondria within eukaryotic cells continuously fuse and divide. This phenomenon is called mitochondrial dynamics and crucial for mitochondrial function and integrity. We performed a comprehensive analysis of mitochondrial dynamics in the pathogenic mold A spergillus fumigatus . Phenotypic characterization of respective mutants revealed the general essentiality of mitochondrial fusion for mitochondrial genome maintenance and the mold's viability. Surprisingly, it turned out that the mitochondrial rhomboid protease Pcp1 and its processing product, s‐Mgm, 1 which are crucial for fusion in yeast, are dispensable for fusion, mtDNA maintenance and viability in A . fumigatus . In contrast, mitochondrial fission mutants show drastically reduced growth and sporulation rates and increased heat susceptibility. However, reliable inheritance of mitochondria to newly formed conidia is ensured. Strikingly, mitochondrial fission mutants show a significant and growth condition‐dependent increase in azole resistance. Parallel disruption of fusion in a fission mutant partially rescues growth and sporulation defects and further increases the azole resistance phenotype. Taken together, our results indicate an emerging dispensability of the mitochondrial rhomboid protease function in mitochondrial fusion, the suitability of mitochondrial fusion machinery as antifungal target and the involvement of mitochondrial dynamics in azole susceptibility. Abstract : Mitochondria form highly dynamic tubular networks that continuously change their shape. In this study we investigated the importance of the mitochondrial fusion and fission processes in the opportunistic human pathogen Aspergillus fumigatus . We show the pivotal role of mitochondrial fusion for maintenance of mtDNA and the mould's viability, the dispensability of the mitochondrial rhomboid protease for fusion, and the involvement of mitochondrial fission in susceptibility to azole antifungals.